A hybrid transition metal nanocrystal-embedded graphitic carbon nitride nanosheet system as a superior oxygen electrocatalyst for rechargeable Zn–air batteries. Issue 38 (23rd September 2020) - Niu, Wen-Jun; He, Jin-Zhong; Wang, Ya-Ping; Sun, Qiao-Qiao; Liu, Wen-Wu; Zhang, Lu-Yin; Liu, Mao-Cheng; Liu, Ming-Jin; Chueh, Yu-Lun
Abstract : A general solid-phase pyrolysis method was developed to synthesize the hybrid transition metals nanocrystals-embedded graphitic carbon nitride nanosheets (M-CNNs) as highly efficient oxygen electrocatalyst for rechargeable Zn–air batteries (ZABs). Abstract : In this study, we, for the first time, demonstrate a general solid-phase pyrolysis method to synthesize hybrid transition metal nanocrystal-embedded graphitic carbon nitride nanosheets, namely M-CNNs, as a highly efficient oxygen electrocatalyst for rechargeable Zn–air batteries (ZABs). The ratios between metallic acetylacetonates and the g-C3 N4 precursor can be controlled where Fe-CNNs−0.7, Ni-CNNs−0.7 and Co-NNs−0.7 composites have been optimized to exhibit superior ORR/OER bifunctional electrocatalytic activities. Specifically, Co-CNNs−0.7 exhibited not only a comparable half-wave potential (0.803 V vs. RHE) to that of the commercial Pt/C catalyst (0.832 V) with a larger current density for the ORR but also a lower overpotential (440 mV) toward the OER compared with the commercial IrO2 catalyst (460 mV), revealing impressive application in rechargeable ZABs. As a result, ZABs using Co-CNNs−0.7 as the cathode exhibited an excellent peak power density of 85.3 mW cm −2 with a specific capacity of 675.7 mA h g −1 and remarkable cycling stability of 1000 cycles, outperforming the commercially available Pt/C + IrO2 catalysts. This study highlights the synergy from heterointerfaces in oxygen electrocatalysis, thus providing a promising approach for advanced metal–air cathode materials.